Effect of Sand and Sand-Lime Piles on the Behavior of Expansive Clay Soil - Mohamed Hussein (Advances in Civil Engineering)
Expansive clay soil causes serious problems to many structures due to its swelling and shrinkage during wet and dry seasons. With the existence of expansive soil in Ahkmim new city, Sohag governorate, Egypt, some light buildings, road pavements, and buried pipelines have shown some damage. To avoid such damage, prior to construction, expansive clay soils should be stabilized. Different methods are available to improve the engineering properties of these soils such as densification, chemical stabilization, reinforcement, and techniques of pore water pressure reduction. The chemical stabilization of clay using lime is one of the widespread methods that can be used to improve the behavior of expansive clay soil. This study aims to investigate the effect of both sand and sand-lime piles on the behavior of expansive clay soil. A series of laboratory tests were carried out using the conventional Oedometer apparatus. Sand piles with different replacement area ratios (RARs) (4.68%, 10.16%, 24.6%, 35.84%, and 56.9%) were used. Also, sand piles stabilized with different percentages of lime (3%, 6%, 9%, 12%, 15%, and 20%) and with a replacement area ratio of 35.84% were used. The experimental results showed there is a significant improvement in reducing the swelling potential of expansive clay soil reinforced with sand or sand-lime piles. This improvement increases with the increase of both replacement area ratio and lime content.